Design of ANFIS based driver fatigue detection system using thermopile and ambient temperature sensors - V Sravan, T.; Madhura, G.; V S K Madhav, G; Sai Sudeep, N; S, Adarsh (International Journal of Engineering and Technology, 2018)
Safety systems play a vital role in automotive industry. Among the safety systems, fatigue detection system is main part in monitoring the level of fatigue of the driver. Vehicle line departure warning system, drivers eye/face monitoring system, steering pattern-monitoring system etc. are a few of the fatigue detection systems deployed in the vehicle by the OEMs (Original Equipment Manufacturers). Lack of proper sleep, sleep apnea, spikes in blood sugar level, anemia etc., are considered as some of reasons for driversâ€™ fatigue. In this paper, we have designed and prototyped a system to monitor the lev-el of fatigue of the driver in real-time. The proposed system uses temperature sensors (thermopile array and ambient temperature sensor) to capture the heat map information of driversâ€™ face and the frequency of yawns. The neuro-fuzzy system in the background processes the data from the sensors for making a logical conclusion â€“ fatigue/ no fatigue. The accuracy of detection can be improved by training the system across multiple subjects. The proposed system was evaluated across various membership functions, for selecting the right membership function.Â